The mainstream of civilization - Strayer, Joseph R. (Joseph Reese), 1904-1987.; Gatzke, Hans Wilhelm, 1915- (New York : Harcourt Brace Jovanovich, 1979)
Traces the history of the world's major civilizations discussing their special characteristics and contributions.
Includes index.
Keywords: Civilization -- History; Civilization -- History